A Performance Measurement Study Using the CRITIC and ARAS Methods in the International Aerospace Industry - Yaşar, Mehmet (International Sustainable Aviation Research Society, 2025)
This study aims to evaluate the performance of manufacturing companies operating in the international aerospace industry. In this context, the financial performance of 12 leading companies from 2019-2023 is analysed through multi-criteria decision-making processes using the CRITIC and ARAS methods. In order to evaluate the performance of the companies in question, a number of financial indicators are taken into consideration, including total capital, capital expenditures, gross income, operating expenses, total liabilities and working capital. The CRITIC method was employed to ascertain the relative importance of the criteria, while the ARAS method was utilised to evaluate the performance of the companies in question. The results demonstrate that the Transdigm Group is the most successful company, with General Electric consistently ranking second. Conversely, the performance of companies such as Airbus and Boeing has exhibited variability over time. The findings of this study offer valuable insights for strategic performance evaluation in the aerospace industry.